Destructive Fibrosarcoma of the Maxillary Sinus. Issue 3 (May 2018) - Ekinci, Adnan; Karataş, Duran; Yetiş, Abdurrahman; Erenler, Behice Hande; Ozcan, Muge
Abstract : Abstract: Paranasal fibrosarcoma of nasal cavity and paranasal sinuses is a very rare malignant tumor. It is usually presented with nasal obstruction and epistaxis. In this clinical report, clinical symptoms, pathogenesis, and treatment principles of a paranasal fibrosarcoma originating from the right maxillary sinus and obstructing the right nasal passage are discussed. A 55-year-old male patient was admitted to the authors clinic with complaints of nasal obstruction and epistaxis lasting for 2 years. Anterior rhinoscopy revealed a mass lesion which obstructed the right nasal passage and caused frequent epistaxis. An opacity consistent with soft tissue lesion which was originated from the right maxillary sinus and filled the right nasal passage was observed in paranasal tomography. Magnetic resonance imaging revealed that the mass lesion was contrasted. Tumor was seen to erode orbital floor, and lateral and anterior walls of the maxillary sinus. Biopsy result was reported as papilloma. The patient was treated with Denker approach as anterior wall of the maxillary sinus was eroded by the tumor lesion and the mass lesion was excised. The patient received postoperative radiotherapy as pathological diagnosis was reported as paranasal fibrosarcoma.